A detailed study of hydrogen bonded ferroelectric mesogens formed between alkyl and alkyloxy benzoic acids with carbamyl glutamic acid. Issue 3 (19th February 2018) - Sangameswari, G.; Pongali Sathya Prabu, N.; Madhu Mohan, M. L. N.
ABSTRACT: A new ferroelectric homologous series of hydrogen-bonded ferroelectric liquid crystals is designed and synthesised with 14 compounds comprising two homologous series. The hydrogen bond is formed between dicarboxylic acid, viz. Carbamyl glutamic acid (CGA) with p-n-alkyl/alkyloxy benzoic acids (BA/BAO) and is confirmed by Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR) studies. These two series referred as the CGA+nBAO and the CGA+nBA yields 14 mesogenic homologues and the mesogenic nature is detected by optical textures through polarising microscope which is confirmed through Differential Scanning Calorimetry (DSC). CGA+nBAO series exhibit cholesteric, smectic X*, smectic C* and smectic G* phases while CGA+nBA exhibits cholesteric and smectic G*phases. The enthalpy values of the corresponding temperatures are elucidated. Odd–even effect is evinced at smectic C* to smectic G* phase transition temperatures of CGA+nBAO series. The order of the individual phase transition and thermal stability factor of the phases is also calculated. Optical tilt angle in smectic C* phase is obtained by optical extinction method. Dielectric relaxation and their corresponding frequency shift observed in different ferroelectric phases are measured and a dielectric molecular modelling is presented. Crystallisation kinetic study of smectic G* phase in CGA+nBAO is computed. An interesting phenomenon – 'Parachromatism' – is elaborated. Graphical Abstract: